MicroRNAs in gastrointestinal cancer: prognostic significance and potential role in chemoresistance. (August 2014) - Hong, Liu; Han, Yu; Yang, Jianjun; Zhang, Hongwei; Zhao, Qingchuan; Wu, Kaichun; Fan, Daiming
Abstract : Introduction: Although chemotherapy is an important therapeutic strategy for gastrointestinal cancer, its clinical effect remains unsatisfied due to drug resistance. Drug resistance is a complex multistep process resulting from deregulated expression of many molecules, including tumor suppressor genes, oncogenes and microRNAs (miRNAs). A better understanding of drug resistance-related miRNAs may eventually lead to optimized therapeutic strategies for cancer patients. Areas covered: This review summarizes the recent advances of drug resistance-related miRNAs in esophageal, gastric and colorectal cancer. Furthermore, this study envisages future developments toward the clinical applications of these miRNAs to cancer therapy. Expert opinion: Drug resistance-related miRNAs may be potentially predicting biomarkers that help guide individualized chemotherapy. Specific miRNAs and their target genes can be used as therapeutic targets by reversing drug resistance. More investigations should be performed to promote the translational bridging of the latest research into clinical application.